PENINGKATAN KEMAMPUAN MENEMUKAN UNSUR-UNSUR INSTRINSIK CERPEN MELALUI MODEL PEMBELAJARAN JIGSAW PADA SISWA KELAS IX.B SMP NEGERI 16 KOTA JAMBI TAHUN AJARAN 2022 - Arita. Sy Arita. Sy (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research aims to describe how to improve the ability to find intrinsic elements of short stories through the Jigsaw learning model in students of SMP Negeri 16 Jambi city in 2022. The research is a class action research with a descriptive survey research method. The number of respondents was 36 students selected based on a simple random sampling technique. The instrument uses a questionnaire on the ability to understand the intrinsic elements of short stories, while the instrument for observing learning performance uses questionnaires. The implementation of research consists of two cycles; each cycle consists of four stages: planning, implementing actions, observation, and reflection. From the study results, an average of 70.32 was obtained in the pre-cyclical period, the learning outcomes test in the first cycle obtained an average rat value of 82.78, and in cycle II, an average rat value of 87.62 was obtained. The learning achievement rate in the new pre-cyclical reached 32.43 percent. After holding class actions in cycle I by applying the Jigsaw learning model, an achievement reached 89%, youthfulness was reflected, and transfer assignments to competent ones and improved learning atmosphere from the aspect of student psychology in cycle II, student achievement reached 100%. Based on this research, it was concluded that by using the Jigsaw learning model, Learning outcomes to understand intrinsic elements can increase.